The Influence of Democratic Leadership Style, Work Motivation, and Rewards on the Work Loyalty of Employees of the Yogyakarta City Fire and Rescue Service - Oktaviana, Annisa; Hadi , Syamsul; Syafwan , Mohammad Ahyar (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to determine how Democratic Leadership Style, Work Motivation, and Rewards influence employee loyalty at the Yogyakarta City Fire and Rescue Department. The saturated sampling methodology was used in this quantitative research analysis. All 54 employees were included in the research sample. One of the analysis techniques used was regression analysis. The research findings indicate that (1) job loyalty is not influenced by democratic leadership style, (2) work motivation has a positive and significant impact on job loyalty, and (3) rewards have a positive but insignificant impact on job loyalty. The F-test analysis of the research yielded the following findings: (4) Democratic leadership style, work motivation, and rewards all have a simultaneous impact on job loyalty. Based on the research findings, organizations are encouraged to adopt a more democratic and participatory leadership style, enhance employee work motivation, and reassess reward structures to maintain and foster employee job loyalty.